Pengaruh Kualitas Jasa Pelayanan Di Hypermart Palangka Raya. - sunarmi . sunarmi; Pamungkur Pamungkur (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2023)
This research was conducted to uncover what consumers really want or expect and what consumers have perceived from the service quality they receive. The purpose of this research were: (1) To determine the factors that affect the quality of service at Hypermart Palangka Raya, (2) To determine what factors have the most influence on customer satisfaction at Hypermart Palangka Raya, (3) To acknowledge the most dominant factor in service provided at Hypermart Palangka Raya. The research employed a descriptive methodology. The data source consisted of responses obtained through a questionnaire given to respondents. The variables used were independent variables, namely: reliability (X1), responsiveness (X2), assurance (X3), empathy (X4), physical evidence (X5) which is the dependent variable is service quality (Y1) and customer satisfaction (Y2). Multiple regression analysis was used for statistical analysis. The findings of this research revealed the following: (1) Among the five variables between tangible, reliability, responsiveness, assurance, and empathy, tangible variable is the positive and significant factor on service quality variables at Hypermart Palangka Raya, (2) The most dominant factor in service quality at Hypermart Palangka Raya, (3) Service quality has a positive and significant effect on customer satisfaction at Hypermart Palangka Raya.